2013
DOI: 10.1002/anie.201307113
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of DNA‐Capped Gold Nanoparticles in High‐Concentration, Divalent Salt Environments

Abstract: The multiparametric nature of nanoparticle self-assembly makes it challenging to circumvent the instabilities that lead to aggregation and achieve crystallization under extreme conditions. By using non-base-pairing DNA as a model ligand instead of the typical base-pairing design for programmability, long-range 2D DNA-gold nanoparticle crystals can be obtained at extremely high salt concentrations and in a divalent salt environment. The interparticle spacings in these 2D nanoparticle crystals can be engineered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
36
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 28 publications
6
36
2
Order By: Relevance
“…In one approach, charged Langmuir monolayers have been used as templates that attract and crystallize capped nanoparticles from solutions [5][6][7]. In a different approach, it has been found that by manipulating salt concentrations in NPs suspensions, a Gibbs-like monolayer can be spontaneously formed and crystallized [8][9][10]. It should be emphasized that for all these assemblies, 2D or 3D, salts play a decisive role in tweaking the charge of the DNA strands and facilitate specific 3D assembly of NPs or migration of NPs to the liquid interface [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one approach, charged Langmuir monolayers have been used as templates that attract and crystallize capped nanoparticles from solutions [5][6][7]. In a different approach, it has been found that by manipulating salt concentrations in NPs suspensions, a Gibbs-like monolayer can be spontaneously formed and crystallized [8][9][10]. It should be emphasized that for all these assemblies, 2D or 3D, salts play a decisive role in tweaking the charge of the DNA strands and facilitate specific 3D assembly of NPs or migration of NPs to the liquid interface [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In a different approach, it has been found that by manipulating salt concentrations in NPs suspensions, a Gibbs-like monolayer can be spontaneously formed and crystallized [8][9][10]. It should be emphasized that for all these assemblies, 2D or 3D, salts play a decisive role in tweaking the charge of the DNA strands and facilitate specific 3D assembly of NPs or migration of NPs to the liquid interface [5][6][7][8][9][10]. In fact, a recent study suggests that the underlying mechanism that drives DNA-capped AuNPs to the surface and to crystallization has to do with the role of salt in tweaking the hydrophobic-hydrophilic character of the DNA-capped AuNPs [10].…”
Section: Introductionmentioning
confidence: 99%
“…Assembling nanoparticles (NPs) into superlattices with specific symmetries is crucial for applications such as catalysis, optical devices, sensors, and energy storage . Although there has been considerable progress in assembling 2D and 3D superlattices of metallic and semiconductor NPs, the challenge of up‐scaling and stabilizing these crystals still remains . In this regard, self‐assembly of NPs driven by interparticle and thermodynamic forces has proven to be a promising approach for the formation of macroscale ordered assemblies …”
mentioning
confidence: 99%
“…For DNA nanotechnology, DNA is always treated as a kind of polymer with four different units (GCAT) randomly coded along the chain . So its physical behavior is sensitive to the details of the design and surrounding environments . In order to form highly ordered lattices, careful design of DNA shells are requisite .…”
Section: Dynamic Superlatticesmentioning
confidence: 99%
“…Moreover, they can help to determine the types and symmetries of the lattices . Researchers investigated a series of factors which could induce the variation of DNA chains bridged between two nanoparticle cores, including ligand length, ionic strength, the interaction between the particles, and so on, in order to fulfill one goal: dynamic control over the behaviors of superlattices.…”
Section: Dynamic Superlatticesmentioning
confidence: 99%